Analasis Sintasan dan Pertumbuhan Kerang Pada Sistem Integrated Agriculture Aquakulture (IAA) Model Floating-Bed Berbasis GIS - Andrian Dwi Dwi Putra; Arnold Kabangga; Nursyahran Nursyahran; Heriansah Heriansah; Is Arianto Pratama (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Fish farming activities in ponds produce waste in the form of feed residues and metabolic products such as urine and feces. To minimize the accumulation of these residual nutrients, an Integrated Multi-Trophic Aquaculture (IMTA) system is applied that combines organisms of different trophic levels: fed organisms (fish, shrimp), organic extractive organisms (sea cucumbers, shellfish, sea urchins), and inorganic extractive organisms (seaweed). This study aims to evaluate the influence of floating-bed-based integrated cultivation system on the survival and growth of kijing clams (Corbicula sp.). The experimental design used a Group Random Design (RAK) with nine units of experimental ponds at the People's Hatchery Unit (UPR) Sipurennu, Soppeng Regency, for 90 days. Three treatments were tested based on floating-bed moving time intervals: A (no displacement), B (10-day replacement), and C (20-day replacement). The main parameter observed was Absolute Weight Growth (PBM). The results showed that the highest PBM was found in treatment B (117.6 g), while the lowest was in treatment A (31.5 g). The ANOVA test showed significant differences between treatments (P<0.05), indicating that the frequency of displacement of extractive species affects the growth rate. In conclusion, the Integrated Agriculture-Aquaculture (IAA) system with a floating-bed model has a significant impact on the survival and growth of kijing mussels through the management of ecological utilization of aquaculture waste